Motor Unit Number Estimation of the Second Lumbrical Muscle in Human Hand - Zong, Ya; Lu, Zhiyuan; Chen, Maoqi; Deng, Lianfu; Xie, Qin; Zhou, Ping (Frontiers in Physiology, 2022)
The number of motor units of the lumbrical muscles in human hand has not been explored. The objective of this study was to fill this gap by estimating the number of motor units in the second lumbrical muscle. Compound muscle action potential (CMAP) scan of the second lumbrical muscle was performed in 12 healthy subjects, with 10 of them being tested on two separate occasions. Motor unit number estimation (MUNE) was derived from the MScanFit program. The average MUNE of the second lumbrical muscle was 41.6 ± 2.1 (mean ± standard error) from 12 subjects in the first test, and 42.0 ± 2.2 from 10 subjects in the retest, demonstrating excellent measurement reliability. Findings of the study provide novel information about the motor unit number of the second lumbrical muscle in human hand. The relatively low motor unit number in the muscle can facilitate motor unit investigations, especially at high level muscle activation.